Extracellular vesicles influence the pulmonary arterial extracellular matrix in congenital diaphragmatic hernia. Issue 9 (8th July 2020) - Monroe, Madeline N.; Zhaorigetu, Siqin; Gupta, Vikas S.; Jin, Di; Givan, Katelyn D.; Curylo, Alexander L.; Olson, Scott D.; Cox, Charles S.; Segura, Ana; Buja, Louis Maximilian; Grande‐Allen, Kathryn Jane; Harting, Matthew T.
Abstract: Objective: Abnormal pulmonary vasculature directly affects the development and progression of congenital diaphragmatic hernia (CDH)‐associated pulmonary hypertension (PH). Though overarching structural and cellular changes in CDH‐affected pulmonary arteries have been documented, the precise role of the extracellular matrix (ECM) in the pulmonary artery (PA) pathophysiology remains undefined. Here, we quantify the structural, compositional, and mechanical CDH‐induced changes in the main and distal PA ECM and investigate the efficacy of mesenchymal stem cell‐derived extracellular vesicles (MSC‐EVs) as a therapy to ameliorate pathological vascular ECM changes. Methods: Pregnant Sprague‐Dawley rodents were administered nitrofen to induce CDH‐affected pulmonary vasculature in the offspring. A portion of CDH‐affected pups was treated with intravenous infusion of MSC‐EVs (1 × 10 10 /mL) upon birth. A suite of histological, mechanical, and transmission electron microscopic analyses were utilized to characterize the PA ECM. Results: The CDH model main PA presented significantly altered characteristics—including greater vessel thickness, greater lysyl oxidase (LOX) expression, and a relatively lower ultimate tensile strength of 13.6 MPa compared to control tissue (25.1 MPa), suggesting that CDH incurs ECM structural disorganization. MSC‐EV treatment demonstrated the potential to reverse CDH‐related changes, particularly through rapid inhibition of ECM remodeling enzymes (LOX and MMP‐9). Additionally, MSC‐EV treatment bolstered structural aspects of the PA ECM and mitigated pathological disorganization as exhibited by increased medial wall thickness and stiffness that, while not significantly altered, trends away from CDH‐affected tissue. Conclusions: These data demonstrate notable ECM remodeling in the CDH pulmonary vasculature, along with the capacity of MSC‐EVs to attenuate pathological ECM remodeling, identifying MSC‐EVs as a potentially efficacious therapeutic for CDH‐associated pulmonary hypertension. Abstract : Schematic of experimental workflow, including treatment conditions and analytical methods employed on harvested pulmonary artery (PA) tissue (CDH = congenital diaphragmatic hernia, CDH – EV = Extracellular vesicle‐treated congenital diaphragmatic hernia).